Validity & Reliability of Teacher Stress Inventory to measure Occupational Stress among Secondary School Teachers in Sri Lanka - E. P. Wickramasinghe; R. De A. Senevirathne; N. S. Gunawardena; A. Sumathipala; C, Mallen (College of Community Physicians of Sri Lanka, 2022)
Introduction: Occupational stress among teachers represents a major global public health issue. Research into the prevalence of occupational stress among secondary teachers in Sri Lanka has not been conducted due to the absence of a valid and reliable instrument to accurately measure teachers occupational stress in the Sri Lankan cultural context. Teacher Stress Inventory (TSI) is a valid and reliable 49-item self-administered tool to assess occupational stress among teachers. Objectives: To translate the TSI to Sinhalese, culturally adapt and to assess its validity, reliability and acceptability among secondary school teachers in Sri Lanka Methods: The TSI was culturally adapted and translated to Sinhala language. This was validated among systematically selected 305 secondary school teachers in Gampaha District. Convergent and discriminant validity was assessed against the validated General Health Questionnaire-30 and Depression Anxiety Stress Scale-21. Conﬁrmatory Factor Analysis (CFA) was performed using LISREL-8.8 to evaluate construct validity. Internal consistency and test-retest reliability and acceptability were assessed simultaneously. Results: The original two-factor model: stressors and manifestations of stress, with model ﬁt indices (GFI=0.76; CFI=0.96; RMSEA=0.065) was considered an appropriately ﬁtting valid model to assess occupational stress. Its reliability was conﬁrmed by good internal consistency (Cronbach's alpha of 0.875) and test-retest reliability (correlation co-efﬁcient of 0.769-0.857). Conclusions & Recommendations: The TSI-Sinhala was found to be a valid, reliable and acceptable tool recommended to estimate occupational stress among secondary school teachers in Sri Lanka. The Department of Education can utilize this tool to assess occupational stress among secondary grade teachers, to take necessary preventative and supportive interventions for teachers who are in need.